Simple Screening of Pulmonary Artery Hypertension Using Standard Chest X Ray: An Old Technique, New Landmark - Mirsadraee, Majid (National Research Institute of Tuberculosis and Lung Disease, 2013)
BACKGROUND: Pulmonary artery hypertension (PAH) is difficult to diagnose because of its nonspecific symptoms. Although echocardiography can reliably and rapidly recognize the presence of pulmonary hypertension, chest X ray (CXR) is more widely used because of its availability. The objective of this study was to find a parameter, which, by changing the scale of CXR, is still useful for detection of PAH. MATERIALS AND METHODS: This case control prospective study included 100 subjects with a clinical finding of dyspnea. Additionally, thirty healthy volunteers (control group) were included in this study. Systolic pulmonary artery pressure (SPAP) was determined by echocardiography. Widening of pulmonary hilum, projection of the right side of the heart border (PRHB) and the ratio of these parameters to the chest diameter were compared to SPAP using the regression method. A cut-off point was determined for parameters that showed significant correlation. RESULTS: The most prevalent disease in the dyspnea group was COPD (28%). Average SPAP was 41.8±17.3 (ranging from 10 to 87 mmHg). Multivariate analysis of the covariance revealed significant correlation between SPAP, age, sex and hilar widening (r = 0.44, P = 0.0001) that was higher than PRHB and hilar widening + PRHB (r= 0.374. and r= 0.438, respectively). The ROC curve showed that the area under the curve was not significantly different for all parameters and the best cut-off point with sensitivity of more than 80% was as follows: hilar size more than 112 mm, PRHB more than 44 and hilum/chest ratio more than 0.44. CONCLUSION: Hilum/chest ratio is the proper substitution for the hilar size in case of changing the scale of the chest X ray. Evaluation of hilar widening and PRHB could lead to identifying more subjects suffering from undiagnosed PAH.